2015
DOI: 10.1016/j.jlp.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated halon replacement agents in explosion inerting

Abstract: The US Federal Aviation Administration (FAA) observed during explosion tests that at low concentrations candidate halon replacement agents increased the explosion severity instead of mitigating the event. At UTC Aerospace Systems a test program was developed to assess the behaviour of alternative agents at values below inerting concentration. Two agents were selected, HFC-125 and Novec ™ 1230. Baseline tests were performed with unsuppressed propane/air mixtures and fuel/air mixtures with Halon 1301 and nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 6 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…The calculated laminar flame speeds of C 6 F 12 O and C 2 HF 5 are 0.367 cm/s and 1.56 cm/s at 400 K, respectively. Gatsonides et al 22 experimentally investigated the fuel-like characteristics of C 6 F 12 O and C 2 HF 5 . They found that the halon agents act similar to fuel in the lean-fuel condition and change the equivalence ratio.…”
Section: Resultsmentioning
confidence: 99%
“…The calculated laminar flame speeds of C 6 F 12 O and C 2 HF 5 are 0.367 cm/s and 1.56 cm/s at 400 K, respectively. Gatsonides et al 22 experimentally investigated the fuel-like characteristics of C 6 F 12 O and C 2 HF 5 . They found that the halon agents act similar to fuel in the lean-fuel condition and change the equivalence ratio.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical 1,1,1,2,2,4,5,5,5-nonafluoro-4-(trifluoromethyl)-3-pentanone, also known as Novec 649, Novec 1230, and FK-5-1-12, is a fully fluorinated ketone that is under development for applications as a working fluid in organic Rankine cycles, as a working fluid in electronics cooling applications, , and as a replacement agent in fire suppression systems. In the heat transfer community, it is typically known as Novec 649, while, in the fire suppression community, it is usually called Novec 1230 or FK-5-1-12. In this manuscript, for convenience, we will refer to this fluid as Novec 649.…”
Section: Introductionmentioning
confidence: 99%
“…Ingerson 13 investigated the fire extinguishing performance of three different Halon substitutes, including FK-5-1-12, on commercial aircraft nacelle fires, and an appropriate concentration of FK-5-1-12 was given, which was equivalent to the concentration of Halon 1301. Gatsonides 14 and Pagliaro 15 experimentally studied how FK-5-1-12 affects the suppression of propane combustion. Other studies [16][17][18][19] measured thermal properties of FK-5-1-12.…”
mentioning
confidence: 99%